PENGARUH PENERAPAN MODEL MIND MAPPING TERHADAP AKTIVITAS BELAJAR SISWA DAN PENGUASAAN MATERI - Destri Eka Nita; Arwin Achmad; Pramudiyanti Pramudiyanti (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2014)
This study aims to determine the effect of mind mapping model towards the activity and mastery of the material by the students in the subject matter of the ecosystem. The study design was a pretest-posttest non equivalent groups. The samples of the research are  VII.j class and VII.i class selected by cluster random sampling. The quantitative data was obtained from the average test score that were analyzed by using the U-test. The qualitative data in the form of student learning activities that were analyzed descriptively. The results showed that the use of mind mapping models of learning can improve the students material mastery, it was seen in the experimental class average value of N-gain of (74.03). In addition, the average student activity also increase (75.49). Based on the result of the study conclude that the use of mind mapping models of learning and improve the mastery of student learning activities.Penelitian ini bertujuan untuk mengetahui pengaruh model mind mapping terhadap aktivitas dan penguasaan materi oleh siswa pada materi pokok ekosistem. Desain penelitian adalah pretes-postes kelompok tak ekuivalen. Sampel penelitian kelas VII.j dan VII.i yang dipilih secara cluster random sampling. Data kuantitatif diperoleh dari rata-rata nilai tes yang dianalisis menggunakan uji-U. Data kualitatif berupa aktivitas belajar siswa yang dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa penggunaan model pembelajaran mind mapping dapat meningkatkan penguasaan materi siswa, ini terlihat pada kelas eksperimen rata-rata nilai N-gain sebesar (74.03). Selain itu, rata-rata aktivitas siswa juga menunjukkan peningkatan sebesar (75.49). Berdasarkan hasil penelitian disimpulkan bahwa penggunaan model pembelajaran mind mapping meningkatkan penguasaan materi dan aktivitas belajar siswa.Kata kunci :aktivitas belajar, ekosistem, mind mapping, penguasaan materi